An Application of Can Slim Investing in the Dow Jones Benchmark - Lutey, Matt; Hassan, Mohammad Kabir; Rayome, Dave (Asian Journal of Economic Modelling, 2018)
This paper provides an alternative view of the popular CAN SLIM investing strategy by modifying and weighting the criterion. The modified criterion is used to build a portfolio in each of three overlapping time frames. The results of the study are compared to a Dow Jones Industrial Average benchmark over the same time frame and is evaluated on a risk adjusted basis. The study finds that the system outperforms the market on a risk adjusted basis in all three time frames and holds a high R Squared for each timeframe. The null hypothesis for the majority of this paper is to test whether the mean returns of the strategy are significantly different from zero on a monthly basis. This is tested over three overlapping timeframes of five years, ten years and sixteen years respectively. A further hypothesis is tested for the 2008-2009 timeframe and is whether the mean excess returns of the strategy are significantly different from zero when compared to the Dow Jones benchmark. This paper finds that the null hypothesis is rejected over all time frames with strong evidence. An exception is the 16-year time frame where the null is rejected with weak evidence.